Knowledge management models - Abdul Kadir, Adibah; Abdul Hamid, Mariam; Md Amin, Noor Dina; Maulad Bahrol, Khadijah; Ismail, Fadillah (Penerbit Uthm, 2019)
Knowledge is basic in regular work. Everybody realizes how to complete his work and this learning can be reused later in comparative undertakings by embracing this information to another circumstance. The universally useful of Knowledge Management (KM) is to make learning usable for more than one individual, for example for an association in general; that is, to share it. New learning put together perspectives with respect to associations recommend that it is information that holds association’s together (Brown & Duguid, 1998).